TINJAUAN TEORITIS PERFORMANSI MESIN BERTEKNOLOGI VVT-i - Tulus Burhanuddin Sitorus (Jurnal Dinamis, 2009)
AbstractTechnology of variable valve timing intelligent (VVT-i) is one of the application of information technology in the automotive industry particularly in terms of engine performance improvements. VVT-i is the valve settings combustion technology. The fundamental difference is owned by VVT-i system is the intake cam rotation need not exactly match the rotation of the engine. In cars without VVT-i system, intake cam has only one valve opening pattern making machines can not maximize engine power when needed and a large force can not minimize the fuel used when the power needed is not large. While in the car with the engine VVT-i technology, when the driver requires a larger force, the valve mechanism will be arranged so that engine torque can be increased. Conversely, when it only takes a little engine power, the valve mechanism will be arranged so that fuel is used much less and of course the resulting exhaust gas cleaner. The results of theoretical studies indicate that the engine with VVT-i technology has torque and the optimal engine power in all conditions and workload with the use of more fuel-efficient.Keywords : VVT-i technolog; Engine performance; Torgue